Rural-to-Urban Migration, Strain, and Juvenile Delinquency: A Study of Eighth-Grade Students in Guangzhou, China. (February 2018) - Lo, Celia C.; Cheng, Tyrone C.; Bohm, Maggie; Zhong, Hua
This examination of minor and serious delinquency among eighth graders in a large southern Chinese city, Guangzhou, also compared groups of these students, observing differences between the delinquency of migrants and that of urban natives. Data used were originally collected for the study "Stuck in the City: Migration and Delinquency Among Migrant Adolescents in Guangzhou." The present study asked whether and how various sources of strain and social control factors explained students' delinquency, questioning how meaningfully migration status moderated several of the observed delinquency relationships. Of students in the sample, 741 reported being natives of Guangzhou, and 497 reported migrating to Guangzhou from a rural area. The study conceptualized internal migration as a strain factor leading to delinquency, but the analyses did not suggest direct association between internal migration and delinquency. Results generally supported Agnew's theory, and, what's more, they tended to confirm that migration status moderated juvenile delinquency.